Identification of a novel PRMD16::SKI fusion gene in T-prolymphocytic leukemia - Brunetti, Marta; Gjelberg, Hilde Kollsete; Reikvam, Håkon; Micci, Francesca (Frontiers in Oncology, 2025)
The presence of the PRDM16::SKI fusion gene was described, for the first time, in a T prolymphocytic leukemia (T-PLL) patient with a long indolent period and a late development treatment requiring disease. The fusion transcript was detected by RNA sequencing and validated by reverse transcriptase polymerase chain reaction and Sanger/Cycle sequencing. The chimera occurs between exon 1 of the PR/SET Domain 16 (PRDM16) gene and exon 2 of the oncogene V-Ski Avian Sarcoma Viral Oncogene Homolog (SKI) gene. The finding provides insight into the role of genetic alterations, including fusion genes, in development and progression of T-PLL and may possibly lead to the development of effective and precise targeted therapy for this disease.